A Comparison of Instantaneous and Extension p-q Methods for Current Controlled Voltage Source Inverter in Microgrid. Issue 11 (2nd November 2022) - R, Vinifa; A, Kavitha; Selwynraj A, Immanuel
ABSTRACT: With the advancement in technology and population growth, the motivation of integrating utility grid with the microgrid through power electronic converters increases. This paper presents the control of power electronic converter connected at the grid side. This converter regulates the power flow between renewable energy system (RES), load and grid in addition to the compensation of harmonic and reactive power. The reference currents are generated to decide the power flow from RES to the load and to suppress the harmonic and reactive power in the grid making grid current sinusoidal. In this paper, the reference current generation techniques like instantaneous real-reactive (p-q) method and extension p-q method are implemented and compared. Linear Quadratic Regulator (LQR) is used to track the reference current. The control law of LQR is designed in a simple way using simplified equivalent circuit of a three-phase grid integrated renewable energy system. The system is tested experimentally under balanced and unbalanced conditions in two different modes such as insufficient renewable power and excess renewable power. The supremacy of extension p-q method over instantaneous p-q method is proved by getting low total harmonic distortion and better power factor under balanced and unbalanced conditions experimentally.